Uso de estruturas de drenagem por jaguatiricas (Leopardus pardalis) em trecho da rodovia BR-101 que intercepta a Reserva Biológica de Sooretama - Barreto, Lucas Mendes (2017)
Habitat fragmentation for road construction and operation can generate a number of impacts at different scales, creating small, isolated subpopulations that can result in disruption of wildlife movements among local populations. Thus the present study aimed to characterize use, the ocelot (Leopardus pardalis), of culvert drainage located on a stretch of BR-101 highway that intersects the Sooretama Biological Reserve. Records obtained from photographic traps were used between December 2014 and December 2015. Identification and individualization were performed through a combination of diagnostic characters. We evaluated the pattern of activity between the traps allocated to drainage structures, access and trails, dry and rainy season, lunar phases, between the sexes and between individuals performing the MardiaWatson-Wheeler test. Total of 612 records were found, and 334 were individualized and distributed in nine specimens, with the period catemeral activity. The periods of activity were significant for: dry and rainy season (W = 14.6, p = 0.0006), new moon phase and full moon (W = 8.64, p = 0.013) and between sex (W = 9.28, p = 0.01). We found a high use of space by the ocelots in the sampled area, identified the use of the area sampled by nine individuals and found a social, spatial organization and differences in the pattern of activity.